Conventional and emerging technologies for removal of antibiotics from wastewater - Phoon, B.L. (Elsevier B.V., 2020)
Antibiotics and pharmaceuticals related products are used to enhance public health and quality of life. The wastewater that is produced from pharmaceutical industries still contains noticeable amount of antibiotics, and this has remained one of the major environmental problems facing public health. The conventional wastewater remediation approach employed by the pharmaceutical industries for the antibiotics wastewater removal is unable to remove the antibiotics completely. Besides, municipal and livestock wastewater also contain unmetabolized antibiotics released by human and animal, respectively. The antibiotic found in wastewater leads to antibiotic resistance challenges, also emergence of superbugs. Currently, numerous technological approaches have been developed to remove antibiotics from the wastewater. Therefore, it was imperative to critically review the weakness and strength of these current advanced technological approaches in use. Besides, the conventional methods for removal of antibiotics such as Klavaroti et al., Homem and Santos also discussed. Although, membrane treatment is discovered as the ultimate choice of approach, to completely remove the antibiotics, while the filtered antibiotics are still retained on the membrane. This study found, hybrid processes to be the best solution antibiotics removal from wastewater. Nevertheless, real-time monitoring system is also recommended to ascertain that, wastewater is cleared of antibiotics. Â© 2020 Elsevier B.V.